Featured Cover. (21st February 2021) - Li, Qiaoru; Li, Bo; Wang, Jingyi; Chang, Xiaoping; Mao, Xinguo; Jing, Ruilian
Abstract : The cover image is based on the Original Research TaPUB15, a U‐Box E3 ubiquitin ligase gene from wheat, enhances salt tolerance in rice by Qiaoru Li et al., https://doi.org/10.1002/fes3.250 .